2002
DOI: 10.1182/blood-2002-01-0008
|View full text |Cite
|
Sign up to set email alerts
|

A molecular compendium of genes expressed in multiple myeloma

Abstract: We have created a molecular resource of genes expressed in primary malignant plasma cells using a combination of cDNA library construction, 5 end single-pass sequencing, bioinformatics, and microarray analysis. In total, we identified 9732 nonredundant expressed genes. This dataset is available as the Myeloma Gene Index (www.uhnres.utoronto.ca/akstewart_lab). Predictably, the sequenced profile of myeloma cDNAs mirrored the known function of immunoglobulin-producing, highrespiratory rate, low-cycling, terminall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 50 publications
(37 reference statements)
9
123
0
3
Order By: Relevance
“…Several studies have demonstrated near universal BCMA expression in PCM cell lines and primary patient PCM cells, and signaling through BCMA provides a survival signal to myeloma cells and promotes resistance to antimyeloma therapies. [92][93][94][95][96] BCMA surface expression appears higher in PCM cells compared with normal plasma cells, and protein expression has not been reported in other normal cells or tissues, other than some mature B-cell subsets and plasmacytoid DC. 97,98 Carpenter et al 97 demonstrated that BCMA-redirected CAR T cells could proliferate, degranulate and produce cytokines when exposed to BCMA-expressing targets and could specifically kill PCM cell lines and primary patient PCM cells.…”
Section: Car T Cellsmentioning
confidence: 97%
“…Several studies have demonstrated near universal BCMA expression in PCM cell lines and primary patient PCM cells, and signaling through BCMA provides a survival signal to myeloma cells and promotes resistance to antimyeloma therapies. [92][93][94][95][96] BCMA surface expression appears higher in PCM cells compared with normal plasma cells, and protein expression has not been reported in other normal cells or tissues, other than some mature B-cell subsets and plasmacytoid DC. 97,98 Carpenter et al 97 demonstrated that BCMA-redirected CAR T cells could proliferate, degranulate and produce cytokines when exposed to BCMA-expressing targets and could specifically kill PCM cell lines and primary patient PCM cells.…”
Section: Car T Cellsmentioning
confidence: 97%
“…In our study, only a single protein band of GAREM was detected in the lysate of certain types of cultured cells such as COS-7, HeLa, 293, and A431 cells (data not shown). The expression of the GAREM gene (FLJ21610) has been identified by microarray analysis of multiple myeloma cells (35). Further, this gene is hypomethylated in various human colorectal carcinoma cell lines (36).…”
Section: Figure 5 Binding Of Shp2 To Garem Upon Egf Stimulationmentioning
confidence: 99%
“…157 In fact, pim-2 is dysregulated in lymphomas, leukemias including AML and several myelomas. [158][159][160][161] It has been postulated that Pim-2 blocks apoptosis. It has been postulated that Pim-2 blocks apoptosis through phosphorylation of the proapoptotic Bad protein.…”
Section: Mechanisms Of Resistance In Amlmentioning
confidence: 99%